The Effect of Al-Quran Murotal Audio Therapy on Sleep Quality in Infants Aged 3-6 Months at the Ananda Clinik Keurukuh - Fitri Hijri Khana; Rika Mursyida; Risna Fazlaini; Rahmatika R (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Background: Sleep quality is one of the essential determinants of infant growth and development because approximately 75% of growth hormone secretion occurs during sleep. Poor sleep quality may negatively affect neurological maturation, cognitive development, immune function, and physical growth. Non-pharmacological interventions, including listening to the recitation of the Holy Qur'an (murottal), have been increasingly used as complementary therapies to promote infant relaxation and improve sleep quality. Objective: This study aimed to determine the effect of Al-Qur'an murottal audio therapy on sleep quality among infants aged 3–6 months at Ananda Clinic, Keurukuh, North Aceh. Methods: A quantitative pre-experimental study with a one-group pretest–posttest design was conducted among 32 infants aged 3–6 months selected using total sampling. Sleep quality was assessed using a modified Sleep Diary questionnaire with a Guttman scale before and after seven consecutive days of Al-Mulk Surah murottal therapy administered for 30 minutes before bedtime. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and the Wilcoxon Signed Rank Test. Results: Before intervention, 59.4% of infants had poor sleep quality, while 40.6% had good sleep quality. After intervention, good sleep quality increased to 93.8%, whereas poor sleep quality decreased to 6.3%. Wilcoxon analysis demonstrated a statistically significant improvement in sleep quality after therapy (mean score 1.41 vs. 1.94; p=0.000). Conclusion: Al-Qur'an murottal audio therapy significantly improves sleep quality among infants aged 3–6 months and may serve as a safe, simple, and effective complementary intervention in maternal and child health services.